27th Congress of the International Society on Thrombosis and Hemostasis - N. V. Seredavkina (Современная ревматология)
The paper presents information on the 27th Congress of the International Society on Thrombosis and Hemostasis, which was held in Melbourne (Australia) in July 2019. This congress is the world’s leading forum on thrombosis and hemostasis, as well as on the causes of bleeding and their clinical manifestations. It unites all specialists who are relevant to this problem.